2010
DOI: 10.3109/00365511003615317
|View full text |Cite
|
Sign up to set email alerts
|

Human trypsinogens in the pancreas and in cancer

Abstract: ISBN 978-952-92-3963-4 (paperback) ISBN 978-952-10-4732-9 (pdf) http://ethesis.helsnki.fi Yliopistopaino Helsinki 20083

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 318 publications
(512 reference statements)
0
8
0
Order By: Relevance
“…In conditions simulating colocalization compartments, activation of anionic trypsinogen was considerably inhibited relative to cationic trypsinogen while the autocatalytic degradation of anionic trypsinogen and trypsin derived from it was 10–20 folds higher (41) indicating that cationic trypsinogen and its trypsin are important players in pathological conditions. In fact, upregulation of anionic trypsinogen reported to occur in pancreatic diseases (45, 46, 60) could be a protective response to limit enzyme activation (41) although upregulation of anionic trypsinogen has also been cited to argue otherwise (52). Using knockout approach, we report that the absence of cationic trypsinogen abrogates pathologic trypsinogen activation, thus clearly establishing that cationic trypsinogen is the isoform that is involved in pathologic intra-acinar enzyme activation during pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In conditions simulating colocalization compartments, activation of anionic trypsinogen was considerably inhibited relative to cationic trypsinogen while the autocatalytic degradation of anionic trypsinogen and trypsin derived from it was 10–20 folds higher (41) indicating that cationic trypsinogen and its trypsin are important players in pathological conditions. In fact, upregulation of anionic trypsinogen reported to occur in pancreatic diseases (45, 46, 60) could be a protective response to limit enzyme activation (41) although upregulation of anionic trypsinogen has also been cited to argue otherwise (52). Using knockout approach, we report that the absence of cationic trypsinogen abrogates pathologic trypsinogen activation, thus clearly establishing that cationic trypsinogen is the isoform that is involved in pathologic intra-acinar enzyme activation during pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the myeloperoxidase/H 2 0 2 /hypochlorous acid (HOCl) system of inflammation induces the oxidative inactivation of TIMPs, whilst promoting the activation of MMPs, at concentrations found during inflammation [184,185], providing mechanisms through which the gelatinase B/MMP-9/TIMP equilibrium within tumours can be altered in favour of proteolytic activity even under conditions of high level TIMP expression [186]. TIMP MMP-inhibitory activity, furthermore, can be destroyed by neutrophil elastase, trypsin and α-chymotrypsin, all of which activate gelatinase B/MMP-9 [12,187,188], providing an additional mechanism for irreversible TIMP inhibition combined with gelatinase B/MMP-9 activation within inflammatory tumour environments and also environments such as the pancreas, in which trypsin and trypsin-like enzymes are expressed [189]. Finally, truncated gelatinase B/MMP-9 isoforms generated by enzymatic digestion or present on the cell surface of human leukemic cells have been shown to escape TIMP inhibition (see Section 3.4).…”
Section: Gelatinase B/mmp-9 Expression Bioavailability Activity mentioning
confidence: 99%
“…AAT can be synthesized by mononuclear cells, alveolar macrophages and epithelial cells and those synthesized by extrahepatic cells play an important role in the regulation of local tissue injury. Our previous work has demonstrated that trypsin can degrade extracellular matrix and basement membrane to promote the occurrence, invasion and metastasis of pancreatic cancer [15,17,21]. The principle of trypsin induces normal cells turning into cancerous ones is that; trypsin activates cell surface transmembrane receptor PAR-2 which promotes the formation of p-ERKI/2.…”
Section: New Interpretation Of Enzymes and Anti-enzyme Imbalance Causmentioning
confidence: 99%
“…Pancreatic secretory trypsin inhibitor (PSTI) also known as serine protease inhibitor Kazal-type 1 (SPINK1) or tumor-associated trypsin inhibitor (TATI) (Account for 20%) and AAT (Account for about 80%) can antagonize against the activity of trypsin in the physiological state, but over expression of AAT can cause immune tolerance of mutant cells [19][20][21][22][23][24]. Therefore, it is necessary to analysis the relation between chain expression of PRSS1, PRSS2, AAT besides TCRVß and the occurrence, invasion and clinical outcome of pancreatic cancer.…”
Section: New Interpretation Of Enzymes and Anti-enzyme Imbalance Causmentioning
confidence: 99%
See 1 more Smart Citation